PENGARUH PESAN PENGINGAT LEWAT APLIKASI BIDANKU TERHADAP KUNJUNGAN ULANG AKSEPTOR KB SUNTIK 1 BULAN DI PMB RENY ROSALINA - Halwani, Horidatul; Sulistiyah, Sulistiyah; Maulina, Rifzul (NHM PRESS, 2024)
Injectable contraceptives are the most popular, but acceptors have to make repeat visits once a month to get an injection so that their contraception is always maintained. However, some side effects can cause birth control acceptors to be reluctant to get repeat injections. The Bidanku application is one way to increase the obedience or compliance of family planning acceptors to make repeat visits. This study aims to determine the effect of reminder messages via the bidanku application on repeat visits by 1-month injection contraceptive acceptors. This research used a quasi-experiment with a two group posttest only design. The research population was all acceptors of 1-month contraceptive injections at PMB Reny Rosalina for the period January-February 2024 with a sample of 32 KB acceptors for 1-month injections consisting of 16 KB acceptors for 1-month injections in the treatment group and 16 acceptors of 1-month contraceptive injections in the control group. Sampling was taken using purposive sampling. Data collection uses observation sheets and family planning cards. Data analysis uses univariate and bivariate analysis. Bivariate analysis with the Mann-Whitney test. The results of the research showed that 28.1% of respondents had re-visits for 1-month injection contraceptive acceptors without using the Midwife app reminder, and 46.9% of respondents had 1-month re-visit for KB injection acceptors using the Midwife app reminder message, 46.9% of respondents were on time. The results of the Mann-Whitney test show that there is an effect of reminder messages via the bidanku application on repeat visits of 1-month contraceptive injection acceptors at PMB Reny Rosalina